Family Therapy dalam Gangguan Emosi dan Kenakalan Remaja Pada Anak dari Lingkungan Lahan Rawa - Zainal Fauzi; Sri Ayatina Hayati (Kuras Institute, 2022)
This study aims to determine family therapy in emotional disorders and juvenile delinquency. This study covers emotional disorders and juvenile delinquency that occur to students. The results of observations and preliminary studies conducted by researchers at MTsN 1 Banjarmasin juvenile delinquency can arise because there is no acceptance, warmth, protection, uncontrolled anxiety development, depressed mood, and psychological stress. This study uses a quantitative approach with experimental methods. In this study, the experimental design used was